Development of Augmented Reality Media to Grow Numerical Literacy of Elementary School Students - Muhammad Ilman Nafian (International Journal of Educatio Elementaria and Psychologia, 2024)
The use of augmented reality (AR) in education has shown potential to improve primary school students' numeracy skills. However, AR research for elementary school geometry is still rare. This study aims to develop augmented reality (AR)-based interactive learning media using the assembler edu platform to improve students' numeracy literacy in geometry subjects. The development method uses ADDIE, the research stages include needs analysis, design, development, implementation, and evaluation. The needs analysis identified problems such as the lack of interactive learning materials and students' difficulties in understanding geometry material. At the design stage, the storyboard and flowchart are made using assembler applications. Media development is done by combining components such as materials, geometry images, animations, and music. Implementation is done through trials by material experts, media experts, and field practitioners, as well as small group and large group trials. The evaluation results show that the developed media has high validity with a percentage of 92% from material experts and 88% from media experts, as well as a significant increase in student numeracy literacy with the percentage of completeness increasing from 6.15% (pre-test) to 79.8% (post-test). With an N-Gain Score of 0.52, this media is proven effective and feasible to use as an additional learning resource.. Recommendations for future research include developing content for other topics, testing in different conditions, and improving interactive features.